2015
DOI: 10.1007/s10551-014-2534-8
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of Responsible Leadership: Asian Versus Western Executive Responsibility Orientations Toward Key Stakeholders

Abstract: Exploring the construct of social-responsibility orientation across three Asian and two Western societies (Germany, Hong Kong, Japan, South Korea, and the United States), we show evidence that top-level executives in these societies hold fundamentally different beliefs about their responsibilities toward different stakeholders, with concomitant implications for their understanding and enactment of responsible leadership. We further find that these variations are more closely aligned with institutional factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 74 publications
1
75
0
Order By: Relevance
“…Furthermore, the well-documented evidence on the negative effects of materialism on environmental ethics clearly delineates its potential repercussions for environmental values, as well as attitude toward TBL (planet). Witt and Stahl's [54] cross-national study also found that stakeholder salience or values (e.g., people and environment) often lies at the bottom of priority list in China, as managers single-mindedly pursue economic values above all functions. Kolodinsky et al [31] also found support for materialism as a leading cause that exerts negative impact on students' business ethics preference with respect to society and environment e.g., community participation and green/eco-friendly manufacturing.…”
Section: Materialism Ethical Values and Tbl Preferencesmentioning
confidence: 99%
“…Furthermore, the well-documented evidence on the negative effects of materialism on environmental ethics clearly delineates its potential repercussions for environmental values, as well as attitude toward TBL (planet). Witt and Stahl's [54] cross-national study also found that stakeholder salience or values (e.g., people and environment) often lies at the bottom of priority list in China, as managers single-mindedly pursue economic values above all functions. Kolodinsky et al [31] also found support for materialism as a leading cause that exerts negative impact on students' business ethics preference with respect to society and environment e.g., community participation and green/eco-friendly manufacturing.…”
Section: Materialism Ethical Values and Tbl Preferencesmentioning
confidence: 99%
“…The philosophical aspect of how leadership and ethics intersect is often satisfied with reference to historical and contemporary 'Greats,' such as Plato (Korabik 1990), MacIntyre (Sinnicks 2016), or Levinas and Gilligan (Grandy and Sliwa 2017). This can extend across cultures, with contributions explaining the ethical particularities of, for example, leadership in non-US (the default culture) countries such as Japan (Taka and Foglia 1994;Witt and Stahl 2016). A related series of contributions bring what are sometimes called 'traditional' (Pava 2001) or faith-based (Wang and Hackett 2016) ethics to understanding leadership.…”
Section: Looking Backmentioning
confidence: 99%
“…These include notions of ethical leadership (Brown et al 2005;Schaubroeck et al 2012;Treviño et al 2003); follower-centric approaches (Shamir and Eilam 2005); responsible leadership (Doh and Quigley 2014;Maak and Pless 2006;Miska and Mendenhall 2015;Pless 2007;Pless and Maak 2011;Pless et al 2012;Voegtlin et al 2012;Waldman and Galvin 2008;Witt and Stahl 2016); servant leadership (Greenleaf 2002); distributed leadership (Bolden 2011); authentic leadership (Endrissat et al 2007;Luthans and Avolio 2003;Michie and Gooty 2005) and transformational leadership (Burns 1978;Ciulla 2004, p. 316). The overlaps and distinctions between these notions of leadership have been identified previously (e.g., Miska and Mendenhall 2015).…”
Section: The Motivating Roles Of Personal Values and Reflexivity In Pmentioning
confidence: 99%
“…Some of these individuals were repeatedly cited by their colleagues as CSR leaders. However, the orientations (Hemingway, 2013;Pless et al 2012;Treviño et al 2003;Witt and Stahl 2016) of these CSR leaders varied, depending on which of the domain(s) of CSR (or which stakeholder group or groups) they championed. Notably, four of these twelve leaders articulated their sense of limitation around the company's commitment to CSR and sustainability.…”
Section: Turning Points and Leadership In Csrmentioning
confidence: 99%
See 1 more Smart Citation